The Role of the Intrauterine Environment in Shaping Childhood and Adolescence Metabolic Outcomes - Asli Derya Kardelen; Feyza Darendeliler (Metabolites)
Emerging research suggests that the intrauterine environment plays a critical role in predisposing individuals to metabolic syndrome (MetS), a constellation of conditions that heightens the risk for heart disease, stroke, and diabetes. Traditionally linked to lifestyle, the risk for MetS is now understood to be also influenced by fetal exposures. The environment in which a child lives offers abundant potential sources that can contribute to an increased risk of developing various diseases, and in some cases, these factors can be avoided. This review integrates findings from both epidemiological and experimental research to underscore the impact of prenatal factors, including maternal nutrition, obesity, gestational diabetes (GDM), and birth size, on the subsequent development of metabolic derangements in offspring, particularly during puberty. The progression of genetic and epigenetic studies has enlightened the pathophysiology of these conditions starting in the intrauterine period and continuing into early life. By examining data and studies, this article elucidates the prenatal influences and underlying mechanisms that contribute to the pathogenesis of MetS. The updated understanding of the link between the intrauterine environment and future health comorbidities will draw attention to intrauterine care and maternal health and contribute to the prevention of serious diseases in adulthood.